Association between Different Domains of Sedentary Behavior and Health-Related Quality of Life in Adults: A Longitudinal Study - Scarabottolo, Catarina Covolo [UNESP]; Tebar, William Rodrigues; Araújo Guerra, Paulo Henrique; Martins, Clarice Maria de Lucena; Ferrari, Gerson; Beretta, Victor Spiandor [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (MDPI, 2022)
Extended periods of time on screen devices and sitting are the main activities that characterize sedentary behavior (SB), which negatively impacts the quality of life. This negative influence was demonstrated mainly by cross-sectional studies performed in high-income countries in which the effects of screen time on health-related quality of life (HRQoL) is not considered. Thus, we analyzed the association between the different domains of SB (i.e., subdomains of screen time—television, computer, cellphone) and the HRQoL in adults that live in Brazil during two years of follow-up. The sample included 331 adults. Subdomains of screen time (i.e., watching television, using computers, and cellphones) and of HRQoL (i.e., physical functioning, role-physical, bodily pain, general health, vitality, social functioning, role-emotional, mental health, and current health perception) were assessed by a structured questionnaire and SF-36, respectively. Our results indicate a significant increase in screen time during the two years of follow-up. Linear regression models indicated that although domains of SB were differently associated with HRQoL, in general, screen time was negatively associated with social functioning and positively associated with physical functioning during locomotion and activities of daily living (ADL), role-physical (i.e., physical issues during work and ADLs), and role-emotional (i.e., emotional issues during work and ADLs) after the two-year follow-up. In conclusion, screen time may positively or negatively influence some domains of HRQoL in adults.
Keywords: emotion; general health; mental health; physical functioning; screen time